A Rare Case of Anti-TIF-1γ Antibody Positive Dermatomyositis in Adulthood - Upasana Agrawal MD; Manush Sondhi MD; Alexandra Zamora Smith MD; Syeda Sara Nida MD; Sarwat Umer MD; Samina Hayat MD; Kinza Muzaffar MD (SAGE Publishing, 2024)
Dermatomyositis (DM) presents with inflammatory myopathy and distinct skin manifestations, often linked to specific autoantibodies. Anti-transcriptional intermediary factor-1 gamma (TIF-1γ) antibodies (Abs) are typically linked to DM in older patients and malignancy in 15% to 40% of cases. We highlight a case of a 24-year-old female who presented with weakness of proximal muscles, periorbital edema, heliotrope rash, erosions on oral mucosa, and painful scaly rash on the lower extremities. Transcriptional intermediary factor-1 gamma Abs were positive, confirming inflammatory myopathy. Treatment with steroid pulse therapy and immunoglobulin led to improvement. Evaluation for malignancy yielded unremarkable results. This case underscores the importance of recognizing and managing DM with TIF-1γ Ab positive, even in atypical demographics, and highlights the need for comprehensive malignancy evaluation.